Environmental and Wastewater Treatment Applications of Stimulus-Responsive Hydrogels - Anita Ioana Visan; Irina Negut (Gels)
Stimulus-responsive hydrogels have emerged as versatile materials for environmental and wastewater treatment applications due to their ability to adapt to changing environmental conditions. This review highlights recent advances in the design, synthesis, and functionalization of such hydrogels, focusing on their environmental applications. Various synthesis techniques, including radical polymerization, grafting, and copolymerization, enable the development of hydrogels with tailored properties such as enhanced adsorption capacity, selectivity, and reusability. The incorporation of nanoparticles and bio-based polymers further improves their structural integrity and pollutant removal efficiency. Key mechanisms such as adsorption, ion exchange, and photodegradation are discussed, emphasizing their roles in removing heavy metals, dyes, and organic pollutants from wastewater. Additionally, this review presents the potential of hydrogels for oil–water separation, pathogen control, and future sustainability through integration into circular economy frameworks. The adaptability, cost-effectiveness, and eco-friendliness of these hydrogels make them promising candidates for large-scale environmental remediation.